Considerations when trying to quantify immersion with secondary tasks - Payne, Emily; Battel, Kayli; Baker, Nancy; Ward, Nathan (Frontiers in Virtual Reality, 2024)
Immersion is a crucial component to characterizing virtual reality (VR) and discovering its many implications for our lives. Studies have defined immersion as the extent that virtual environments submerge users' perceptual systems, shut out the physical environments' inputs, and induce engrossment in users. The present study sought to further understand the applications of immersion in virtual environments by leveraging traditional self-report measures, as well as investigating the use of distraction to quantify immersion objectively. We hypothesized that participants in immersive 3-dimensional VR would self-report higher levels of immersion and engagement compared to a non-VR condition. We also predicted that participants in the VR condition would have impaired responses to a secondary task compared to the non-VR condition. Using a within-subjects design, participants engaged in a VR meditation both on a computer screen (non-VR) and through a VR headset (VR). During the meditations, they completed a secondary detection-response task (DRT) by pressing a button in response to a tactile stimulus. We used DRT reaction times to objectively measure immersion. Following the meditations, participants completed questionnaires regarding their experiences. As predicted, participants reported that the VR condition increased their engagement and presence compared to the non-VR version of the same meditation scenario. With regard to the secondary detection task, we did not find a significant effect of VR on DRT performance, although DRT performance was numerically worse in the VR condition compared to the non-VR condition. These mixed results suggest that the use of a secondary task depends upon several factors, which we discuss.